REWORK COST ON BUILDING PROJECTS IN THE SOUTH WESTERN PART OF NIGERIA - Olatunji Ayodeji Aiyetan (Journal of Construction Project Management and Innovation)
Right-first-time is a principle that evaluates the competence of firms, quality of product and the expertise of a professional. Rework is doing something at least one extra time due to nonconformance to requirements, could suggest the abovementioned parameter negatively either on organisation or individual. Human beings are not perfect, based on this, errors occur that may lead to rework on site and should be accommodated adequately for an uninterrupted flow of construction activities and non-delay of delivery of projects. The south western part of Nigeria was the area of study. The quantitative and descriptive research approaches were used. The questionnaire survey and historical data were the two method used for the collection of data for the study. Simple statistical means were used for data analysis. The research findings indicate that incorrect lying of forming course, poor quality of concrete, poor plastering, and construction errors during excavation dominate relative to areas of rework. Therefore, the study suggests that in order to eliminate or reduced drastically the occurrence of rework on future projects, consideration should be given to the following: the setting aside of a sum of money equal to the value of 0.6 – 5.0% of initial contract sum, engagement of knowledgeable foremen or having regular training of foremen, the correct construction processes should be followed in the execution of construction activities, and materials that are of good quality only should be used for constructional purposes.